2019
DOI: 10.3389/fnbeh.2019.00254
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of the Unconditioned Stimulus Inhibits the Return of Fear Independent of Cortisol

Abstract: Reconsolidation is the post-retrieval stabilization of memories, a time-limited process during which reactivated (i.e., retrieved) memories can be updated with new information, become stronger or weaker, depending on the specific treatment. We have previously shown that the stress hormone cortisol has an enhancing effect on the reconsolidation of fear memories in men. This effect was specific, i.e., limited to the conditioned stimulus (CS) that was reactivated, and did not generalize to other previously reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…In contrast, exposure to mild stress led to a fear memory impairment in men (possibly through an interruption of memory reconsolidation: Meir Drexler and Wolf, 2017b). Moreover, while the previous studies used the commonly used CS-based reconsolidation paradigm (i.e., reactivation by a single unreinforced CS presentation), in an alternative UCS-based reconsolidation paradigm (i.e., through a single weaker UCS presentation), the reactivation method itself prevented the return of fear regardless of the pharmacological (cortisol or placebo) treatment (Meir Drexler et al, 2019b).…”
Section: Cortisol and Memory Reconsolidationmentioning
confidence: 99%
“…In contrast, exposure to mild stress led to a fear memory impairment in men (possibly through an interruption of memory reconsolidation: Meir Drexler and Wolf, 2017b). Moreover, while the previous studies used the commonly used CS-based reconsolidation paradigm (i.e., reactivation by a single unreinforced CS presentation), in an alternative UCS-based reconsolidation paradigm (i.e., through a single weaker UCS presentation), the reactivation method itself prevented the return of fear regardless of the pharmacological (cortisol or placebo) treatment (Meir Drexler et al, 2019b).…”
Section: Cortisol and Memory Reconsolidationmentioning
confidence: 99%
“…This indicates that CS exposure renders fear memory vulnerable to the effects of propranolol, thereby reducing fear response. A low-intensity US can also induce prediction errors 34 . We speculate that US retrieval generates larger prediction errors than CS retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…Building upon these findings, Meir Drexler et al [138] continued investigating the impact of cortisol and US reactivation on fear memory reconsolidation in male participants. The previous findings indicated that differences in cortisol effects on fear memory reconsolidation might exist between men and women.…”
Section: Glucocorticoids and Gender Influence On Fear Extinctionmentioning
confidence: 99%